Setting up and selling a transitional bank as a means of bringing the activity of an insolvent bank to the requirements of economic standards - Ігор Йосипович Петрик (Проблеми Законності, 2020)
The article is devoted to the study of the ways of economic rehabilitation of insolvent banking institution. A special place in the work belongs to the issues of establishment and sale of a transitional bank as a means of bringing the activity of an insolvent bank to the requirements of economic standards. Attention is drawn to the debatable nature of the economic and legal subjectivity of the Deposit Guarantee Fund of Ukraine in the stated procedure. Among other things, the characteristic of economic standards of banking activity is given and the importance of liquidity assessment in the systemic characteristic of the bank is noted. It is pointed out that the procedure for setting up and selling a transition bank is in line with the EU standards as for the rehabilitation of credit institutions and the withdrawal of them from the market.